Overall Equipment Efficiency (Oee) Improvement Through Integrating Quality Tool: Case Study - A. P., Puvanasvaran (2012)
The purpose of this paper is to develop a macro framework that involving the implementation of integrating quality tools on improving Overall Equipment Efficiency (OEE) in autoclave study as to achieve the world benchmark of Overall Equipment Efficiency. A refinement of existing concept of OEE approach is developed primarily based on literature review. The methodology would be used as a set of standard operating procedures to be followed along project flow. The primarily procedures designed on emphasizing the observation and the empirically collected data, while implementation of quality tools are on analyzing the problem found in the previous stage of study and proposed alternative remedies to optimize the OEE. OEE as core quality tool in this study used to monitor the performance and measure the effectiveness of the autoclave curing process in order to achieve the world rating of OEE benchmark. This paper discussed on the implementation of integrating several quality tools which focus mainly to improve the current performance of OEE.